2022
DOI: 10.1007/s12035-022-03111-y
|View full text |Cite
|
Sign up to set email alerts
|

Protein Expression of Amino Acid Transporters Is Altered in Isolated Cerebral Microvessels of 5xFAD Mouse Model of Alzheimer’s Disease

Abstract: Membrane transporters such as ATP-binding cassette (ABC) and solute carrier (SLC) transporters expressed at the neurovascular unit (NVU) play an important role in drug delivery to the brain and have been demonstrated to be involved in Alzheimer’s disease (AD) pathogenesis. However, our knowledge of quantitative changes in transporter absolute protein expression and functionality in vivo in NVU in AD patients and animal models is limited. The study aim was to investigate alterations in protein expression of ABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
(140 reference statements)
1
12
0
Order By: Relevance
“…The SLC group of membrane transport proteins includes over 400 members mostly located in the cell membrane. In line with our results, a study reported that the expression of SLC3A2 was elevated in the isolated brain microvessels of a mouse model of familial AD [49] and in the brain cortical tissue of male TgF344-AD rats [50] compared to respective controls. We also found the downregulation of SLC4A10.…”
Section: Discussionsupporting
confidence: 92%
“…The SLC group of membrane transport proteins includes over 400 members mostly located in the cell membrane. In line with our results, a study reported that the expression of SLC3A2 was elevated in the isolated brain microvessels of a mouse model of familial AD [49] and in the brain cortical tissue of male TgF344-AD rats [50] compared to respective controls. We also found the downregulation of SLC4A10.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the large neutral amino acids transporter small subunit 1 (LAT1) was less expressed in the 5xFAD mouse brain microvessels. However, when compared to humans, the expression of cerebrovascular LAT1 was not different between cognitively normal and AD subjects, although both species had high levels of phenylalanine in the brain, suggesting differences in LAT1 function in the microvessels between mice and humans [104]. Besides glucose and amino acid transporters, the expression of lactate transporters is altered in AD.…”
Section: Slc Transportersmentioning
confidence: 87%
“…Furthermore, the dysregulation of amino acid transporters has been reported. For example, in isolated microvessels from brains of 5xFAD, an AD mouse model, the expression of the transporter alanine/serine/cysteine/threonine transporter (ASCT1) is two times higher than that in the isolated brain microvessels of the wild-type mouse [104]. On the other hand, the large neutral amino acids transporter small subunit 1 (LAT1) was less expressed in the 5xFAD mouse brain microvessels.…”
Section: Slc Transportersmentioning
confidence: 99%
“…Transgenic 5xFAD carrying human APP with the APP Swedish, Florida, and London mutations, as well as human PSEN1 with the M146L and L286V mutations, which were driven by the mouse Thy1 promoter were used in the study ( Jawhar et al, 2012 ). The genotyping was performed according to the procedure described previously ( Puris et al, 2023 ). All mice were 7-month-old males ( n = 8).…”
Section: Methodsmentioning
confidence: 99%
“…At 7 months old, 5xFAD mice possess several important pathological features of AD such as a rapid plaque development of amyloid plaque pathology, astrogliosis and microgliosis proportional to amyloid deposition, neurodegeneration, neuronal loss, deficits in synaptic transmission, spatial memory deficits and cognitive impairment ( Oakley et al, 2006 ; Forner et al, 2021 ; Shin et al, 2021 ). Here, we quantified and compared protein expression levels of three ABC and five SLC transporters in the cortices of 7-month-old male 5xFAD mice versus sex-matched WT controls using previously developed sensitive liquid chromatography with tandem mass spectrometry (LC–MS/MS)-based quantitative targeted absolute proteomics methods ( Puris et al, 2022a ; Puris et al, 2023 ). The changes in absolute protein expression of the transporters were then compared to those in the brain cortical tissue of 7-month-old female mice, which we previously reported ( Puris et al, 2022c ) in order to identify sex-specific alterations in transporter expression in 5xFAD mice.…”
Section: Introductionmentioning
confidence: 99%